The Effects of Curcumin Against Dengue-2 Virus Based on Immunocytochemistry Technique - Dewi Marbawati; Sitti Rahmah Umniyati (Pusat Kedokteran Tropis, 2013)
ABSTRACT Introduction: Dengue is the most important mosquito-borne flavivirus disease. The number of Dengue cases in Indonesia in 2010 range from 150,000 cases with the deaths of around 1,317 people. Huge number of cases have made Indonesia was the first ranked as the state with the highest Dengue cases in the ASEAN region and the world's second ranking after Brazil. The drugs or antibiotics that can be administered effectively to cure this disease has not been found yet. Many study have been done and some that have been reported include viral RNA synthesis inhibitors, protein inhibitors of NS3 helicase and protease and inhibitors that inhibit Dengue virus maturation. Curcumin have preventive activity against several viruses: vasicular stomatis ( VSV ), HSV 1 and 2, parainfluenza - 3, reovirus - 1, feline corona virus, feline herpes virus . Curcumin also known have ubiquitin proteasome inhibition system was able to decrease the production of Japanese ensefalitis virus.Objectives: This study aims to determine safe concentrations of curcumin against vero cells (cytotoxic test results) and know the Dengue-2 antiviral potency of curcumin.Methods: Including quasi-experimental study. The anti viral potency of curcumin seen from the result of immunocytochemistry Streptavidin Biotin Peroxidase Complex (SBPC). Data were analyzed by ANOVA.Results: The results showed that secure concentrations from cytotoxic of curcumin against vero cells is 6.25 ppm. The calculation of positive rate from immunocytochemistry in vero cells infected by Dengue - 2 incubation 1 and 3 days were the result is significantly different than the control.Conclusion: The secure concentration of curcumin against vero cells was 6.25 ppm and curcumin was able to lower the positive rate due to Dengue-2 infection.Key Words : Dengue virus, Curcumin, Immunocytochemistry.